Interparental violence: child emotional awareness, protective factors, and symptom profiles in a comparative analysis - Ortiz Jiménez, Eva M.; Gómez -Benito, Juana; Llach, Selene Liz; Lamarca, María; Ochoa, Susana (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to analyze the differences between children exposed to interparental violence (EIPV) and non-EIPV children aged 8-12, in a) Emotional awareness (EA), b) Protective factors of resilience (external and internal) c) Externalizing/internalizing symptoms, somatic complaints and moods.MethodA descriptive design study was conducted with a total of 115 participants (60 boys and 55 girls) from three Child and Adolescent Mental Health Centers in the metropolitan area of Barcelona, Spain. Student’s t-test was used to compare the EIPV and non-EIPV groups, and logistic regression models were employed to identify the most relevant factors associated with EIPV.ResultsEIPV children exhibited significantly lower scores in differentiating emotions (DIE) and analyzing one’s own emotions (ANE) compared to non-EIPV children. Additionally, EIPV children demonstrated more social skills problems, lower loneliness/social anxiety, lower resilience, mainly in empathy and internal protective factors, autonomy, and reduced self-esteem. They also reported higher levels of externalizing and internalizing symptoms, somatic complaints, and negative mood states such as fear, sadness, and anger. The variables that explained group membership in EIPV were DIE, ANE, and total externalizing symptoms.ConclusionsThis study provides valuable insights into the role of EA, symptoms, and protective factors in EIPV children in a clinical sample. Lower EA, fewer protective factors, and higher levels of internalizing and externalizing symptoms in EIPV children when compared to their non-EIPV counterparts. Including a structures evaluation of EA and Protective Factors in the EIPV child population would improve diagnostic accuracy of trauma and the design of specific psychotherapies interventions aimed at reducing symptoms and promoting mental well-being in children aged 8 to 12 exposed to IPV.